Hubungan Adiksi Game Online dengan Kualitas Tidur pada Anak di SMP Teratai Putih Global Bekasi Tahun 2020 - Khadijah Ratna Widiyani, (2020)
Technology advancement that wasn't dealt with wisely could lead to some problems, one of the example is online game addiction, a global sensation that spread through even to Indonesia. There are 4,388 millions of internet user all over the world, with a penetration of 57%, and 30% of them use the internet to play games online, with the prevalention of internet addiction in teenagers higher in Asian countries rather than in America or Europe. One of the symptoms of online game addiction is spanding and wasting too much time in playing online games resulting in lack of sleep and poor sleep quality that could hinder daily function. This study was done to determine the association between online game addiction and sleep quality of children at SMP Teratai Putih Global Bekasi. This is an observational analytic study with cross-sectional design using validated Indonesian Online Game Addiction Questionnaire and Pittsburgh Sleep Quality Index. There are a total of 51 samples in the study, the sampling was done with stratified random sampling. The result of the bivariate analysis in this study is that there is a significant association between online game addiction and sleep quality (p = 0,001, CI = 95%) of children at SMP Teratai Putih Global Bekasi 2020. Only a few research have been conducted on the association between online game addiction and sleep quality, there's not enough scientific explanation on the phenomenon, so further research is needed.